Exclusive Breastfeeding Determinants in Breastfeeding Mother - Ika Mustika (Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
Exclusive breastfeeding until 6 month is very important for baby. The proportion of mothers who exclusively breastfeed their babies up to 6 months remains low. Factors influencing the exclusive breastfeeding namely sociodemograph factors , factors pre / post delivery , and psychosocial factors. This aims of this study to identify determinant factors of exclusive breastfeeding on mother. This research method is a systematic review , by analyzing the various studies on exclusive breastfeeding. There are 17 studies. The results obtained occupational factors most studied with significant results ( median OR = 1.265 ). Psychosocial factors that have significant relationship is support of her husband (average OR = 4.716 ) and family support ( average OR = 1.770 ). Conclusions : factors influencing the exclusive breastfeeding is occupational factor. Socialization and support from people nearby, health workers, and all parties is needed for exclusive breastfeeding for six months can be achieved.